Research on the evolution and improvement of China’s shadow education governance policy from the perspective of multiple streams theory - Xiang, Kemi; Liu, Jinsi; Chen, Xinzhong; Zhang, Anlu (Frontiers in Psychology, 2023)
From a global perspective, after-school tutoring education, also known as shadow education, has developed rapidly since the beginning of this century. However, shadow education has also brought many practical problems, such as the increased burden on parents and children, and the unfairness in education. At present, the Chinese government is vigorously implementing the double reduction policy and has achieved remarkable practical results. This study focuses on the evolution of the government policy of shadow education in China. First, it analyzed the four stages of shadow education governance policy experience: the acquiescent survival stage, the encouraging development stage, the preliminary regulation stage, and the comprehensive rectification stage. Python was used for text mining the policies from different periods and analyzing the focus of the policies in different stages by obtaining high-frequency vocabulary. Then, the multiple streams theory was used to explore the policy evolution process and change mechanism. Finally, relevant recommendations have been discussed to address the gaps in the current shadow education governance policies. The study found that the objectives, scope of adjustment, and protection of rights and interests of China’s shadow education governance policies have undergone significant changes over time. Through the constant interaction and interweaving of the stream of problems, the stream of politics, and the stream of policy, the window of opportunity for policy change was jointly promoted. The innovations of this article mainly include the following: First, the evolution of China’s shadow education governance policies was systematically reviewed using text mining methods to compare the differences of governance policies at different stages and second, multiple streams theory was used as the theoretical framework to analyze the reasons for the focus of shadow education governance policy changes.